2018
DOI: 10.1002/adhm.201800103
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Bacterial Infections and Biofilm Formation Using Nanoparticles and Nanostructured Antibacterial Surfaces

Abstract: With the rapid spreading of resistance among common bacterial pathogens, bacterial infections, especially antibiotic-resistant bacterial infections, have drawn much attention worldwide. In light of this, nanoparticles, including metal and metal oxide nanoparticles, liposomes, polymersomes, and solid lipid nanoparticles, have been increasingly exploited as both efficient antimicrobials themselves or as delivery platforms to enhance the effectiveness of existing antibiotics. In addition to the emergence of wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(118 citation statements)
references
References 318 publications
(326 reference statements)
0
108
0
Order By: Relevance
“…In addition to the emergence of antibiotic resistance, concerns have also been raised for infections associated with a variety of medical devices including joint prostheses, heart valves, pacemakers and catheters [3]. Device-associated infections are typically caused by microorganisms that grow in biofilms, and are introduced via surgery or implants [4,5]. Treatment of these infections are generally more challenging and require prolonged antibiotic therapy and even revision surgeries, which is inevitably associated with increased patient suffering and high costs [6].…”
Section: Rising Concerns Of Bacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the emergence of antibiotic resistance, concerns have also been raised for infections associated with a variety of medical devices including joint prostheses, heart valves, pacemakers and catheters [3]. Device-associated infections are typically caused by microorganisms that grow in biofilms, and are introduced via surgery or implants [4,5]. Treatment of these infections are generally more challenging and require prolonged antibiotic therapy and even revision surgeries, which is inevitably associated with increased patient suffering and high costs [6].…”
Section: Rising Concerns Of Bacterial Infectionsmentioning
confidence: 99%
“…For instance, using a microfluidic device to control spatial structure and chemical communication, it was found that stable coexistence of interacting bacteria requires a defined microscale structure [236]. Recent advances in material sciences also revealed that a reduction of bacterial adhesion can be achieved via the control of surface topography [5], further confirming the role of physiochemical regulation of biofilm formation. Growing ex vivo samples in vitro also allows for more controlled and reproducible experimental conditions, and permits real-time monitoring of the biofilm progression using techniques like optical coherence tomography [58].…”
Section: Ex Vivo Modelsmentioning
confidence: 99%
“…Interestingly, several studies speculated that metals and metal oxide NPs utilize multiple mechanisms simultaneously in the microbial combating battle, placing MDR microorganisms in a critical position to develop resistance. However, antibiotics, especially bacterial drugs, induce cell death by cell wall inhibition (ÎČ-lactams), RNA synthesis (rifamycins), DNA replication (quinolones), or protein synthesis (macrolides) [8]. In this context, The US FDA has already approved some metal oxides such as ZnO as safe antimicrobial agents against bacteria, fungi, and virus [9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the vesicles that are composed of lipid molecules, the polymer vesicles are more stable. The structural features of hydrophobic membranes and hydrophilic interiors render special chemical and physiological advantages for the delivery of different cargos simultaneously . To explore the application of polymer vesicles for the co‐delivery of antimicrobial agents, a diblock copolymer of methoxypoly(ethelyne glycol)‐ b ‐poly( d )‐( l )‐lactic acid (mPEG‐ b ‐PDLLA) was synthesized for fabrication of polymer vesicles, and two antimicrobial agents, AgNPs and ampicillin, were incorporated into the polymer vesicles for the treatment of antibiotic‐resistant bacterial infections.…”
Section: Biodegradable Polymeric Nanosystems Containing Antibioticsmentioning
confidence: 99%